A conductive folding metamaterial via laser-induced biomimetic electrospinning - Kangze Dong; Guangtao Zan; Xiaoge Mao; Hongmin Zhou; Huasen Wang; Qingsheng Wu; Tong Wu (Proceedings of the National Academy of Sciences, 2025)
Conductive folding metamaterials (CFMs) represent a class of cross-physical-domain new-type metamaterials. However, the inherently nonfoldable nature of intrinsic conductive materials and the incompatibility between conductivity and extreme foldability have posed formidable challenges for their design and fabrication. To overcome these limitations, we developed a laser–electric-field coupled biomimetic spinning (LECBS) technique, which couples laser induction with cocoon/lotus-root-inspired biomimicry in a fast electrospinning Taylor cone reaction. Using this approach, we report the fabrication of CFMs composed of hierarchically adaptive carbon nanofiber networks. The CFMs constitute a new class of artificially microstructured composites with extraordinary physical properties absent in nature, filling a critical gap in the metamaterials family. The resulting CFMs endure up to 10 7 cycles, and potentially unlimited cycles, of true folding without damage, in arbitrary directions and with unrestricted 360° flexibility. Simultaneously, they achieve electrical conductivities on the order of 10 3 S·m − 1 , nearly one order of magnitude higher than comparable systems without carbon nanotubes. Mechanistic studies reveal that LECBS can effectively modulate Taylor cone hydrodynamics and jet behavior through photo-electro-matter interactions, which yields thinner nanofibers, enhanced sliding freedom of nanofibers, and axial alignment of CNTs in carbon nanofibers. Real-time SEM observations demonstrate the formation of characteristic M-shaped creases with “separated layers–smooth arcs–slidable grooves” during folding, which successfully disperse stress, in excellent agreement with finite element simulations. This work not only represents a breakthrough in metamaterials but also a technological revolution, opening new opportunities for flexible and foldable electronics fields.